The Influence of Reading Literacy Culture on Reading Interest of Class V Students at MI Negeri 3 Pekanbaru - Vara, Fasera Utari; Dafit, Febrina (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research was motivated by the less than optimal implementation of a reading literacy culture at MI Negeri 3 Pekanbaru. Even though the school has implemented a reading literacy culture, fifth grade students still face challenges in increasing their interest in reading. The obstacles in implementing this are the lack of interest of students, low enjoyment of reading, and lack of awareness of the importance of literacy. However, the school always tries to facilitate students to develop an interest in reading. This research aims to identify how much influence reading literacy culture has on the reading interest of class V students at MI Negeri 3 Pekanbaru. Through a quantitative approach with an ex post facto research design. The population used in this research was class V students, totaling 103 students. By using the Slovin formula and a confidence level of 10%, a sample of 52 people was obtained. Data collection techniques are carried out through questionnaires, instrument testing uses validity and reliability. The data analysis technique uses descriptive analysis and prerequisite tests, namely normality and homogeneity tests, hypothesis testing in the form of a simple liner regression test using the conditions Ha is accepted and Ho is rejected. Based on data processing from research results with a sample size of 52 class V students at MI Negeri 3 Pekanbaru, it can be concluded that there is a positive and significant influence between the implementation of a reading literacy culture on the reading interest of students in class VMI Negeri 3 Pekanbaru, in other words the proposed hypothesis accepted, namely Ha is accepted and Ho is rejected. As the total influence is 0.331 with the influence being positive. This means that the better the reading literacy culture, the better the students' interest in reading.